CTAB-Assisted Hydrothermal Synthesis of Bi2Sn2O7 Photocatalyst and Its Highly Efficient Degradation of Organic Dye under Visible-Light Irradiation - Weicheng Xu; Zhang Liu; Jianzhang Fang; Guangyin Zhou; Xiaoting Hong; Shuxing Wu; Ximiao Zhu; YunFang Chen; Chaoping Cen (International Journal of Photoenergy)
Pyrochlore-type Bi2Sn2O7 (BSO) nanoparticles have been prepared by a hydrothermal method assisted with a cationic surfactant cetyltrimethylammonium bromide (CTAB). These BSO products were characterized by powder X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET), and UV-visible diffuse reflectance spectroscopy (DRS). The results indicated that CTAB alters the surface parameters and the morphology and enhances the photoinduced charge separation rate of BSO. The photocatalytic degradation test using rhodamine B as a model pollutant showed that the photocatalytic activity of the BSO assisted with CTAB was two times that of the reference BSO. Close investigation revealed that the size, the band gap, the structure, and the existence of impurity level played an important role in the photocatalytic activities.